Ambient VOCs in residential areas near a large-scale petrochemical complex: Spatiotemporal variation, source apportionment and health risk. (September 2018) - Hsu, Chin-Yu; Chiang, Hung-Che; Shie, Ruei-Hao; Ku, Chun-Hung; Lin, Tzu-Yu; Chen, Mu-Jean; Chen, Nai-Tzu; Chen, Yu-Cheng
Abstract: This study investigated ambient volatile organic compounds (VOCs) and assessed excess health risks for child, adult and elderly populations in a residential area near a large-scale petrochemical complex in central Taiwan. A total of 155 daily VOC samples were collected in canisters from nine sites in spring, summer and winter during 2013–2014. We used a positive matrix factorization (PMF) model incorporating a conditional probability function (CPF) to quantify the potential sources of VOCs with the influences of local source directions. We then evaluated the non-cancer and cancer risks of specific VOCs with probabilistic distributions by performing a Monte-Carlo simulation for the child, adult, and elderly populations. Most of the VOCs were higher in summer than in winter or spring for the sampling sites. The presence of vinyl acetate, chloroethene, and 1, 2-dichloroethane were significantly high within a 5-km radius of the petrochemical complex. Four potential sources of ambient VOCs, industrial emission (49.2%–63.6%), traffic-related emission (13.9%–19.1%), fuel evaporation (12.3%–16.9%), and aged emission (10.2%–14.8%), were identified. The cancer risk of ambient VOC exposure was mainly attributed to the industrial source in the study area, while the non-cancer risk was of less concern. Benzene associated with fuel evaporation resulted in the highest cancer risk (4.1 × 10 −5 −5.5 × 10 −5 ) as compared to that of the other toxic VOCs. Graphical abstract: Image 1 Highlights: Spatiotemporal variation of VOCs were comprehensively investigated. The distinct VOCs derived from the petrochemical complex were identified. VOC concentrations in the summer was higher than the spring and winter. The industrial source was the most important contributor. Benzene associated fuel evaporation can lead the highest cancer risk. Abstract : Benzene predominantly attributed to fuel evaporation can lead to the highest cancer risk among VOCs in a residential area near a large-scale petrochemical complex.